The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/su15010633
|View full text |Cite
|
Sign up to set email alerts
|

Technology in Nature—mDGBL as a Successful Approach to Promote Complex Contents?

Abstract: The central challenges of our time mostly share a high level of complexity, which makes them unsolvable by single-perspective approaches. To offer adolescents the educational concepts that enable them to take various perspectives, comprehend, and finally deal constructively with these problems, innovative measures must be created. Additionally, the benefit of these measures must be shared equally by all learners, without being limited by their individual biographical or attitudinal characteristics. In this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The SENSO‐Trail can be explored as a field trip in the real forest or a virtual field trip, SENSO‐Trail360 (public demo version: http://85.214.136.59/). The SENSO‐Trail was evaluated with pupils aged 15–17 in an intervention study and was found to be an effective and robust tool for learning (Bengel & Peter, 2023).…”
Section: The Nature 40 Projectmentioning
confidence: 99%
See 2 more Smart Citations
“…The SENSO‐Trail can be explored as a field trip in the real forest or a virtual field trip, SENSO‐Trail360 (public demo version: http://85.214.136.59/). The SENSO‐Trail was evaluated with pupils aged 15–17 in an intervention study and was found to be an effective and robust tool for learning (Bengel & Peter, 2023).…”
Section: The Nature 40 Projectmentioning
confidence: 99%
“…The SENSO‐Trail uses a multi‐perspective approach (Schmayl, 1995) to break down the content complexity of the Nature 4.0 project, raise awareness, and promote subject‐specific knowledge and scientific literacy (Bengel & Peter, 2023). Datasets from the Nature 4.0 project can be accessed in the SENSO‐Trail and individual reflection is used to contextualize the learning experience.…”
Section: The Nature 40 Projectmentioning
confidence: 99%
See 1 more Smart Citation